(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The purpose of the study was to determine food security through homestead vegetable production. The study was conducted in the Bhaluka, Trishal and Gaforgaon upazilas of Mymensingh district, which were the project areas of the Smallholder Agricultural Improvement Project (SAIP). Sixty (60) respondents were randomly selected from the beneficiaries of SAIP. Data were collected by face-to-face interview with the help of interview schedule. Most of the respondents were middle-aged having small farm size and primary level education. Vegetable production, consumption and calorie uptake of the respondent were increased by 56%, 55% and 68%, respectively, after implementation of demonstration. All the respondents are following the ‘Kalikapur’ model. Nutrient contribution from the produced vegetables through homestead vegetable production fulfilled the 100% Recommended Dietary Allowance (RDA) requirements of vitamin A, vitamin C, and iron, also 87% of calcium and 47% of protein. Four vegetable crops i.e. red amaranth, cabbage, tomato and batishak were introduced into the existing cropping pattern. Changes in social and livelihood issues of a respondent were satisfactory after demonstration. Majority of the respondents (45%) earned satisfactory annual income having homestead. Shortage of irrigation water, quality seeds and inputs cost were the major problems faced by the farmers in homestead vegetable production. Keywords: Food Security; Homestead vegetables DOI: 10.3329/jbau.v6i2.4820 J. Bangladesh Agril. Univ. 6(2): 261-269, 2008